PERANGKAT-PERANGKAT KONSTRUKSI HUKUM ISLAM - Chamim, M. (Irtifaq, 2015)
A construction of thought certainly has a number of important devices that became a cornerstone of thought itself, no exception in Islamic legal thought. Devices construction of Islamic law is the first and foremost element of Islamic law before being applied to the mah}kum fi>h. There are three devices that became a cornerstone of the construction of Islamic Law, namely: (1) h}ukm/hukum, (2) h}a>kim, (3) mah}kum ‘alayh.. Despite talk of Islamic Law, however, is ultimately up to the implementation to mah}kum fi>h. But on the other hand, the application was actually determined by the readiness of the devices construction. This paper focuses on the discussion of the three sets of construction of Islamic Law and the implications arising from differences related to the understanding of three construction device of Islamic Law itself. Keywords : hukum, h}a>kim, mah}kum ’alayh